In vivo affinity and target engagement in skin and blood in a first‐time‐in‐human study of an anti‐oncostatin M monoclonal antibody - Reid, Juliet; Zamuner, Stefano; Edwards, Ken; Rumley, Sally‐Anne; Nevin, Katherine; Feeney, Maria; Zecchin, Chiara; Fernando, Disala; Wisniacki, Nicolas (British journal of clinical pharmacology, 2018)
Aims The oncostatin M (OSM) pathway drives fibrosis, inflammation and vasculopathy, and is a potential therapeutic target for inflammatory and fibrotic diseases. The aim of this first‐time‐in‐human experimental medicine study was to assess the safety, tolerability, pharmacokinetics and target engagement of single subcutaneous doses of GSK2330811, an anti‐OSM monoclonal antibody, in healthy subjects. Methods This was a phase I, randomized, double‐blind, placebo‐controlled, single‐dose escalation, first‐time‐in‐human study of subcutaneously administered GSK2330811 in healthy adults (NCT02386436). Safety and tolerability, GSK2330811 pharmacokinetic profile, OSM levels in blood and skin, and the potential for antidrug antibody formation were assessed. The in vivo affinity of GSK2330811 for OSM and target engagement in serum and skin blister fluid (obtained via a skin suction blister model) were estimated using target‐mediated drug disposition (TMDD) models in combination with compartmental and physiology‐based pharmacokinetic (PBPK) models. Results Thirty subjects were randomized to receive GSK2330811 and 10 to placebo in this completed study. GSK2330811 demonstrated a favourable safety profile in healthy subjects; no adverse events were serious or led to withdrawal. There were no clinically relevant trends in change from baseline in laboratory values, with the exception of a reversible dose‐dependent reduction in platelet count. GSK2330811 exhibited linear pharmacokinetics over the dose range 0.1–6 mg kg–1. The estimated in vivo affinity (nM) of GSK2330811 for OSM was 0.568 [95% confidence interval (CI) 0.455, 0.710] in the compartmental with TMDD model and 0.629 (95% CI 0.494, 0.802) using the minimal PBPK with TMDD model. Conclusions Single subcutaneous doses of GSK2330811 were well tolerated in healthy subjects. GSK2330811 demonstrated sufficient affinity to achieve target engagement in systemic circulation and target skin tissue, supporting the progression of GSK2330811 clinical development.